2011
DOI: 10.1002/ejoc.201100153
|View full text |Cite
|
Sign up to set email alerts
|

Bromination of Tocopherols: Oxidative Halogenations and Rearrangements

Abstract: The bromination behaviour of all four tocopherols and the corresponding model compounds in acidic and basic aqueous media was studied. Acidic conditions resulted in quinones and brominated quinones, with the bromination of the tocopherol preceeding the oxidation to the quinone. Buffer type and concentration did not influence the reaction results, whereas pH and the ratio of buffer and ethanol used as a cosolvent strongly affected the reaction rates. In alkaline media, two or three major products and a multitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…[17] Except for the permethylated a-tocopherol, compounds 2-4 are known to undergo aromatic electrophilic substitution. In this way, bromo-, [18] nitro-, [19] nitroso-, [20] mercury- [20] and aminomethyl groups [21] were introduced into the non-a-tocopherols. To the best of our knowledge, chalcogen substituents were not previously introduced in this way into the tocopherol scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Except for the permethylated a-tocopherol, compounds 2-4 are known to undergo aromatic electrophilic substitution. In this way, bromo-, [18] nitro-, [19] nitroso-, [20] mercury- [20] and aminomethyl groups [21] were introduced into the non-a-tocopherols. To the best of our knowledge, chalcogen substituents were not previously introduced in this way into the tocopherol scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the oxidative halogenation of organic compounds by halides have emerged as an important alternative for the synthesis of such haloderivatives. [19][20][21][22][23][24][25][26][27][28][29][30] Despite the broad choice of options, however, many bromination and iodination methodologies are cumbersome, costly and harsh or involve the use of toxic heavy metals, volatile organic solvents, or elemental halogenes which are highly corrosive, toxic or self-sublimating. In addition, there are some environmental hazards with respect to handling them.…”
Section: Introductionmentioning
confidence: 99%
“…Bohmdorfer, et al found that in case of a-tocopherol, halogenating effect is minor and the major pathway is the oxidative action resulting in the para-quinone. 52 Hence, the bromination is mainly observed by the resorcinol instead of a-tocopherol. Further, it is observed that increasing the concentration of TFMBA up to 0.005 mol L À1 and for b-carotene up to 0.0005 mol L À1 completely quenches the oscillations.…”
Section: Antioxidants In Acetonitrile Based Mediamentioning
confidence: 99%